THE EFFECT OF USING BANANA PEEL IN THE RATION ON KARKAS AND COMMERCIAL PIECES CARCASS OF JOPER CHICKEN - K.R., Noviyanti; Nuriyasa, I M.; Puger, A. W. (Jurnal Peternakan Tropika; Vol 11 No 1 (2023): Vol. 11 No. 1 Tahun 2023; January - april, 2023)
This study aims to determine the effect of the use of fermented banana peel in the ration on carcasses and commercial pieces of joper chicken.  The research was conducted in Tabanan for 8 weeks.  The study used a completely randomized design (CRD), with 4 treatments and 5 replications.  Each experimental unit used 3 joper chickens so that a total of 60 joper chickens were used.  The ration treatment consisted of: TP: the use of 0% fermented banana peel in the ration; P1: the use of 3% fermented banana peel in the ration; P2: the use of 6% fermented banana peel in the ration; P3: the use of 9% fermented banana peel in the ration.  Banana peel fermentation was carried out with EM4 material.  The Variables observed included slaughter weight, carcass weight, carcass percentage, and the percentage of commercial pieces of carcasses (chest percentage, wing percentage, thigh percentage, drumstick percentage, and back percentage).  The results showed that the weight of the carcass and the percentage of carcasses in the treatment of P1 and P2 were actually higher (P<0.05) than TP, while in P3 showed an unreal difference result (P>0.05).  Commercial deductions of carcasses on P1, P2, and P3 treatments show no noticeable difference (P>0.05) with TP.  In the results of the study, it can be concluded that the use of fermented banana peels in rations by as much as 6% can increase the weight of carcasses and the percentage of carcasses in joper chicken, but give the same result to commercial pieces of joper chicken carcasses.   Keywords : joper chicken , fermented banana peel, carcass, carcass commercial pieces